2015
DOI: 10.4238/2015.october.5.17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the drug-resistant characteristics of Klebsiella pneumoniae isolated from the respiratory tract and CTX-M ESBL genes

Abstract: ABSTRACT. The main aim of this study was to understand the relationship between the drug-resistant characteristics of Klebsiella pneumoniae and CTX-M-type extended spectrum β-lactamases (ESBLs), and to detect the distributions of CTX-M-type ESBLs in clinically isolated strains. CTX-M ESBL genes isolated from the clinical samples were amplified by polymerase chain reaction and identified by sequence analysis; the antibiotic susceptibility of the samples was determined using the Kirby-Bauer disc-diffusion method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, it is dissimilar with other studies which showed that the isolates exhibited similar resistance pattern to both ceftazidime and ceftriaxone [ 28 , 29 ]. It was also reported that Klebsiella pneumoniae strain isolated from patients with community acquired pneumonia was resistant to third-generation cephalosporins [ 30 , 31 ]. This is because these strains have a β -lactam ring provided with a Zwitterionic structure that protects these antibiotics from hydrolysis by β -lactamases [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is dissimilar with other studies which showed that the isolates exhibited similar resistance pattern to both ceftazidime and ceftriaxone [ 28 , 29 ]. It was also reported that Klebsiella pneumoniae strain isolated from patients with community acquired pneumonia was resistant to third-generation cephalosporins [ 30 , 31 ]. This is because these strains have a β -lactam ring provided with a Zwitterionic structure that protects these antibiotics from hydrolysis by β -lactamases [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, predominant CTX-M-type ESBLs have been described globally, including China, South Korea, and many other countries 11,31,32. In fact, together with bla CTX-M-14 , bla CTX-M-15 is currently the most common variant detected worldwide in clinically important Gram-negative bacteria 33,34.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the actual location of the ESBL and AmpC β-lactamase genes were not determined in our study. Although it has been shown that ESBL genes could reside on the chromosome40, several studies on ESBL-producing K. pneumoniae have found CTX-M-type and SHV-type ESBL genes to be mostly located on plasmids41424344. Furthermore, the great genotypic diversity of our ESBL and/or AmpC β-lactamase-producers, having different combinations of ESBL/AmpC β-lactamase genes even among isolates within the same PFGE cluster, implied that these resistant genes are acquired through transfer of plasmids among isolates of different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%